Correction of thrombohemorrhagic syndrome in patients with widespread soft tissue phlegmon and sepsis - E. A. Tseimakh; V. Yu. Zinchenko; O. Yu. Lavrinenko; V. V. Chernenko; A. V. Kalashnikov; E. A. Shalabod; M. E. Tseimakh (Исследования и практика в медицине, 2022)
Purpose of the study. Analysis of the effectiveness of cryoprecipitate – antienzymatic with common soft tissue phlegmon and sepsis.Patients and methods. To achieve the intended goal, a study of the results of treatment of 92 patients with a diagnosis of advanced soft tissue phlegmon and sepsis was performed. All patients underwent a comprehensive diagnostic study with an in-depth study of the indicators of the hemostasis system. For a comparative assessment, 2 groups of patients were identified. Group 1 (46 (50 %) patients – the main one) – received cryoprecipitate-antienzymatic therapy as part of complex treatment, group 2 (46 (50 %) patients – comparisons) – received only the generally accepted basic treatment.Results. An in-depth study of the hemostasis system in patients with widespread soft tissue phlegmon and sepsis indicated the development of thrombohemorrhagic syndrome, which was manifested by depletion of both the coagulation and anticoagulation systems of the blood, a drop in AT III, an increase in thrombinemia and fibrinolysis depression. In order to correct thrombohemorrhagic syndrome, a cryoprecipitate-antienzymatic complex was included in the complex treatment of patients with widespread soft tissue phlegmons and sepsis, aimed at unblocking microcirculation in inflammatory foci and parenchymal organs, to improve the penetration of antibacterial drugs and other drugs into these foci, thereby stopping inflammation and preventing the increase of multiple organ failure. The effectiveness of the cryoprecipitate-antienzymatic complex was evaluated based on clinical data of the course of the purulent – inflammatory process and the results of indicators of the hemocoagulation and fibrinolysis system on 8–10 days from the start of therapy.Conclusion. The use of cryoprecipitate-antienzymatic complex, which includes freshly frozen plasma (FFP), heparin, proteinase inhibitors, in patients with widespread soft tissue phlegmon and sepsis effectively eliminates thrombohemorrhagic syndrome, which improves microcirculation in purulent – inflammatory foci and affected parenchymal organs, improving the flow of antibacterial drugs into these foci. At the same time, there is an improvement in the course of the wound process, so the wounds are cleaned faster from necrotic masses and filled with healthy granulation tissue, which makes it possible to perform plastic closure of the wound defect 1.6 times faster. Mortality is reduced by 2.2 times and the number of thrombotic and thromboembolic complications in the structure of deaths is reduced.